Turbidite paleoseismology along the active continental margin of Chile – Feasible or not?. (15th July 2015) - Bernhardt, Anne; Melnick, Daniel; Hebbeln, Dierk; Lückge, Andreas; Strecker, Manfred R.
Abstract: Much progress has been made in estimating recurrence intervals of great and giant subduction earthquakes using terrestrial, lacustrine, and marine paleoseismic archives. Recent detailed records suggest these earthquakes may have variable recurrence periods and magnitudes forming supercycles. Understanding seismic supercycles requires long paleoseismic archives that record timing and magnitude of such events. Turbidite paleoseismic archives may potentially extend past earthquake records to the Pleistocene and can thus complement commonly shorter-term terrestrial archives. However, in order to unambiguously establish recurring seismicity as a trigger mechanism for turbidity currents, synchronous deposition of turbidites in widely spaced, isolated depocenters has to be ascertained. Furthermore, characteristics that predispose a seismically active continental margin to turbidite paleoseismology and the correct sample site selection have to be taken into account. Here we analyze 8 marine sediment cores along 950 km of the Chile margin to test for the feasibility of compiling detailed and continuous paleoseismic records based on turbidites. Our results suggest that the deposition of areally widespread, synchronous turbidites triggered by seismicity is largely controlled by sediment supply and, hence, the climatic and geomorphic conditions of the adjacent subaerial setting. The feasibility of compiling a turbidite paleoseismic record depends on the delicate balance between sufficient sediment supply providing material to fail frequently during seismic shaking and sufficiently low sedimentation rates to allow for coeval accumulation of planktonic foraminifera for high-resolution radiocarbon dating. We conclude that offshore northern central Chile (29–32.5°S) Holocene turbidite paleoseismology is not feasible, because sediment supply from the semi-arid mainland is low and almost no Holocene turbidity-current deposits are found in the cores. In contrast, in the humid region between 36 and 38°S frequent Holocene turbidite deposition may generally correspond to paleoseismic events. However, high terrigenous sedimentation rates prevent high-resolution radiocarbon dating. The climatic transition region between 32.5 and 36°S appears to be best suited for turbidite paleoseismology. Highlights: We test whether turbidite paleoseismology can be applied along the Chile margin. Onshore climate sets the boundary conditions for turbidite distribution and datability. Feasibility depends on the balance between sediment supply and sufficient material for 14 C-dating. A Holocene (late Pleistocene) turbidite paleoseismic record may be established ∼34–36°S (∼32.5°S). Between 18.5–32°S and 36–42°S, turbidite paleoseismology cannot be applied.